Microcontroller based proportional derivative plus conditional integral controller for electro-mechanical dual acting pulley continuously variable transmission ratio control - Budianto, A.; Kamarul Baharin, Tawi; M., Hussein; Supriyo, Bambang; Ariyono, S.; M. S., Che Kob; Mohd Ezlamy, Zulkifli; Khairuldean, A. K.; Aishah, Daraoh (IOP Publishing, 2012)
Electro-Mechanical Dual Acting Pulley (EMDAP) Continuously Variable Transmission (CVT) is a transmission utilized by electro-mechanical actuated system. It has a potential to reduce energy consumption because it only needs power during changing CVT ratio and no power is needed to maintain CVT ratio due to self lock mechanism design. This paper proposed simple proportional derivative plus conditional integral (PDCI) controller to control EMDAP CVT ratio which can be simply implemented on a microcontroller. This proposed controller used Astrom-Hagglund method and Ziegler-Nichols formula to tune PDCI gain. The Proportional Derivative controller is directly activated from the start but Integral controller is only activated when the error value reaches error value setting point. Simulation using Matlab/Simulink software was conducted to evaluate PDCI system performance. The simulation results showed PDCI controller has ability to perform maximum overshoot 0.1%, 0.001 steady state error and 0.5s settling time. For clamping condition, settling time is about 11.46s during changing ratio from 2.0 to 0.7, while for release condition, settling time is about 8.33s during changing ratio from 0.7 to 2.0.